An exploratory study of financial access along the renewable energy sector value chain: the case of SMMEs in South Africa - Mali, Nwabisa (Graduate School of Business (GSB), 2025)
This research explored the financial challenges encountered by small and medium-sized enterprises (SMMEs) in South Africa's renewable energy sector, with a specific focus on access to finance. The study aimed to provide practical recommendations to assist SMMEs in overcoming financial barriers and promoting sustainable growth within the sector. This research sought to address the gap in existing research on financial accessibility for renewable energy SMMEs and highlight strategies that could empower these businesses to thrive in a developing market. A qualitative research approach was adopted, aligning with an interpretivist philosophy to explore participants' experiences and insights. The research strategy involved a case study design, which allowed for a comprehensive and detailed examination of financial access challenges specific to the South African renewable energy sector. Data collection was conducted through face-to-face, semi-structured interviews. The target population consisted of SMME managers and business owners involved in renewable energy sub-sectors, including solar, wind, and biomass energy. The sample comprised 15 participants, selected through purposive sampling to ensure representation across different types of renewable energy enterprises. The sample size was determined based on theoretical saturation, a point at which no new themes or insights emerged from the data, ensuring comprehensiveness of the findings. Thematic analysis of the data identified five main themes: financial stability and revenue streams, financial management practices, market demand, operational costs and market conditions. The findings highlighted that financial stability was closely tied to project scale, with larger-scale projects providing more consistent revenue streams, while SMMEs in niche sectors often faced revenue variability. Financial management practices were essential for sustaining operations, particularly in managing costs and planning for fluctuating revenues. Additionally, market demand fluctuations, high operational costs, and broader economic conditions posed significant financial challenges. The study identified various barriers to financial access, such as stringent lending criteria and high collateral requirements, and evaluated alternative financing options, including venture capital, crowdfunding and government support. Recommendations were provided for policymakers and industry stakeholders to improve financial accessibility, including through policy modifications and development of targeted support programs. Overall, this research contributes to an understanding of the financial dynamics of renewable energy SMMEs in South Africa and offers actionable insights into strategies to foster resilience and sustainable growth within the renewable energy sector.